Cadangan Premi Asuransi Jiwa Berjangka dan Asuransi Jiwa Dwiguna Menggunakan Metode Premium Sufficiency - Gusvira Widuri; Devni Prima Sari (Journal of Mathematics UNP, 2023)
Life insurance is the payment of money given from the death of insured to the heirs according to the provisions of the polis. The are four types of life insurance, namely whole life insurance, term life insurance, and endowment life insurance. The amount of compensation obtained depends on the amount of premium paid. The benefit of paying premiums is as preparation for the payment of the sum assured. The company needs to prepare a reserve fund called a premium reserve which is needed to cover claims of insurance participants that can occur at any time. There are several ways to calculate premium reserves, one of which can be used is the premium sufficiency method. Finding out how to calculate premium reserves using the premium sufficiency approach is the goal of this study. The calculation of reserves using the premium sufficiency method uses a gross premium which can provide a clear indication of the total cost required and the amount of reserves that the insurance company must provide.